Strategic Research Plan Based on Quality Function Deployment (QFD) to Maximize Value Capture and Benefits - Mantari Laureano, Jose Luis (2025)
The Strategic Research Plan (PEI) is an essential tool, which defines roles and sets of actions that any Academic Institution must carry out. One of the priorities for academic organizations and especially for universities, is the formation of human capital. That training must develop the research and innovation capabilities of its graduates, to create, generate ventures, transfer and apply new knowledge. Various techniques can be used to prepare the PEI; however, Quality Function Deployment (QFD) includes the voice of the customer and is very effective for developing a PEI. With the use of the QFD it was obtained: the lines of investigation, the processes of planning, design, monitoring and control based on the requirements of CONCYTEC (the voice of the client). Finally, a PEI aligned with the CONCYTEC requirements is justified, thus increasing the possibilities of being able to obtain research funds that support and promote the research of an academic institution.